Tluyim Bahavir - Katz, Ramy A. (Israel, 2011)
Ahead of his father's release from prison, the virtual reality of the Parkour world in which Avshalom is a super hero, starts to crack. The inevitable upcoming show down with the man he testified against, is going to dictate his mother's fate
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films